Novel In-Office Technique for Visual Confirmation of Demodex Infestation in Blepharitic Patients. Issue 7 (July 2020) - Man Peles, Inbal; Zahavi, Alon; Chemodanova, Elena; Vardizer, Yoav
Abstract : Purpose: To determine whether Demodex infestation in blepharitic patients can be confirmed by slit-lamp examination without the need for light microscopy. Methods: Demodex infestation was evaluated in 16 patients presenting with blepharitis and cylindrical dandruff at a single medical center from November 2014 to February 2015. Two lashes with cylindrical dandruff were epilated from each lid (8 per patient, total 128), mounted on slides, and examined in the clinic under a slit lamp equipped with a 90D condensing lens followed by light microscopy in the pathology laboratory. All evaluations were performed by the same pathologist. Mites were identified by their characteristic morphology and movement patterns. Findings were compared between the 2 methods. Results: The mean total Demodex count per lash was 1.5 ± 2.1 mites by using the slit lamp and 2 ± 2.9 mites by light microscopy. Corresponding counts per patient were 11.7 ± 9.4 and 16.1 ± 12.4. The correlation between the slit lamp and microscopy results was statistically significant, per lash (r = 0.922, P < 0.01) and per patient (r = 0.976, P < 0.01). On analysis by the more clinically relevant negative (no mites detected) or positive results (at least 1 mite detected), the accuracy of the slit-lamp examination for a single lash was 91.4% and the specificity and sensitivity were 89% and 94%, respectively; the negative predictive value was 93% [χ 2 (1) = 87.94, P < 0.01)]. All 16 patients were positive for Demodex infestation by both methods (accuracy 100%). Conclusions: Demodex infestation in blepharitic patients with cylindrical dandruff can be confirmed using only a slit lamp and common eye clinic equipment.